ANALISIS IKLAN DI MADIUN DAN PENGGUNAANNYA DALAM PEMBELAJARAN BAHASA INDONESIA DI SD LEMBAH 02 - Hartoko; Jeffry Handhika; Dwi Rosita Sari (CV Edujavare Publishing, 2026)
This study explores the linguistic features of advertisements found in Madiun and examines how these advertisements can be utilized effectively in Bahasa Indonesia instruction at SD Lembah 02. Using a qualitative case study approach, data were collected through content analysis of 30 advertisements (print, outdoor, and digital), classroom observations, interviews with one Bahasa Indonesia teacher and 12 students (grades IV–V), and analysis of lesson plans and student works. Data were analyzed thematically focusing on (1) linguistic and rhetorical features of ads, and (2) pedagogical practices and potentials for classroom implementation. Results show that advertisements in Madiun commonly employ persuasive devices (slogans, imperatives, hyperbole), concise lexical choices, and visual–verbal interplay that are highly suitable for teaching vocabulary, text structures of persuasive texts, critical literacy, and students’ writing production. The study proposes a set of model activities and assessment rubrics for integrating local advertisements into Bahasa Indonesia lessons to enhance relevance, motivation, and communicative competence.